1990
DOI: 10.1079/bjn19900044
|View full text |Cite
|
Sign up to set email alerts
|

Level of nutrition and visceral organ size and metabolic activity in sheep

Abstract: Thirty-two crossbred wether lambs (initial live-weight 31 kg) were fed on a diet (metabolizable energy (ME) 12.8 MJ/kg) ad lib. (ADLIB) or restricted to maintain body-weight (MAINT) for a 21 d period.On days 0,7,14 and 21, four lambs per treatment were slaughtered, visceral organs weighed and tissues sampled. During the 21 d period, M E intake in ADLIB lambs increased quadratically with an average rate of live-weight gain of 425 g/d. In MAINT lambs, live weight (30 kg) was maintained, and daily M E intake (kJ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

18
104
2
3

Year Published

2000
2000
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(127 citation statements)
references
References 32 publications
18
104
2
3
Order By: Relevance
“…The general linear increases of BW gain, ADG, and HCW validated our nutritional model by following the concept that animal growth rate will be increased by increased intake level of the given diet (National Research Council 1996). The observed increase of visceral organ weight with increasing DMI was consistent with previous reports (Burrin et al 1990;Rompala et al 1991;Fluharty and McClure 1997;Swanson et al 2000;Kelly et al 2001). In agreement with the findings of Burrin et al (1990), the relative proportion of total visceral organ weight to body mass was influenced by feed intake level in the present study.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The general linear increases of BW gain, ADG, and HCW validated our nutritional model by following the concept that animal growth rate will be increased by increased intake level of the given diet (National Research Council 1996). The observed increase of visceral organ weight with increasing DMI was consistent with previous reports (Burrin et al 1990;Rompala et al 1991;Fluharty and McClure 1997;Swanson et al 2000;Kelly et al 2001). In agreement with the findings of Burrin et al (1990), the relative proportion of total visceral organ weight to body mass was influenced by feed intake level in the present study.…”
Section: Discussionsupporting
confidence: 83%
“…Visceral organs and tissues require differing amounts of nutrients to support energy utilization involved in the physiological processes of digestion, absorption, and metabolism. The effect of level of feed intake on changes in the relative contribution of visceral organs to whole-body energy expenditure appears to be primarily a result of differences in organ size rather than tissue-specific metabolic activity (Burrin et al 1990;Kelly et al 2001). However, little is known about dietary factors regulating visceral mass and energy metabolism at the cellular and molecular levels, especially in beef cattle.…”
mentioning
confidence: 99%
“…The reductions in EBW and liver mass due to nutrient Table 1 restriction are consistent with previous reports [21,22]. In concordance with Burrin et al [21], these findings showed that liver mass (e.g., reduced cell size and/or number) changed more rapidly than body weight in response to undernutrition, illustrating the ability of these tissues to adapt rapidly to changing nutrient supply.…”
Section: Discussionsupporting
confidence: 82%
“…In concordance with Burrin et al [21], these findings showed that liver mass (e.g., reduced cell size and/or number) changed more rapidly than body weight in response to undernutrition, illustrating the ability of these tissues to adapt rapidly to changing nutrient supply. In ruminants, portal blood flow is known to vary with metabolizable energy intake [1,23], thus, in underfed animals, blood flow is reduced, leading to decreased liver nutrient absorption and in consequence a decreased liver mass.…”
Section: Discussionsupporting
confidence: 77%
“…T he portal-drained viscera (PDV; the intestines, pancreas, spleen, and stomach) contribute between 20% and 35% of whole-body energy expenditure and protein synthesis, even though they contribute less than 6% of body weight (1)(2)(3). Dietary amino acid use by the intestine could have a substantial effect on their systemic availability and thereby regulate wholebody protein deposition.…”
mentioning
confidence: 99%